Characterisation and classification of the physical deterioration of tropically weathered kenny hill rock for civil works - Zainab Mohamed, Abd Ghani Rafek, Ibrahim Komoo, . (2007)
An appreciation to the concept of rock weathering is vital for engineer in order for him to achieve sustainability in design and construction of geotechnical structure in tropical environment. The study is to characterize and classify the physical deterioration of tropically weathered Kenny hill weak rock. The objective is to demonstrate the significant influence of tropical rock weathering in civil engineering works